Bioaccumulation and biotransformation of inorganic arsenic in zhikong scallop (Chlamys farreri) after waterborne exposure. (August 2021) - Zhao, Yanfang; Kang, Xuming; Ding, Haiyan; Ning, Jinsong; Zhai, Yuxiu; Sheng, Xiaofeng
Abstract: Arsenic (As) and As speciation in marine bivalves have been widely investigated. However, little is known about the bioaccumulation and biotransformation of inorganic As in different tissues of scallops. Therefore, the tissue-specific accumulation, biotransformation and subcellular partitioning of As were investigated in Chlamys farreri following 12 d inorganic As [arsenite (AsⅢ) and arsenate (AsⅤ)] exposure and 30 d depuration. Total As levels were highest in the kidneys and lowest in the adductor muscle after 12 d exposure for both As (Ⅲ) and As (Ⅴ) treatment groups, and the bioavailability of As (Ⅲ) was significantly higher than that of As (Ⅴ) for C. farreri . After 30 d elimination, total As levels were significantly decreased to the control levels. The subcellular fate of As in five different tissues was similar for different inorganic As treatment groups. The greatest proportion of As was found in the metallothionein-like protein fraction (MTLP) and the second was the cellular debris (CD). A little part of As (Ⅲ) could be oxidized to As (Ⅴ) in the gill and digestive gland for As (Ⅲ) treatment groups, and the reduction of As (Ⅴ) to As (Ⅲ) happened in the gill and kidney under As (Ⅴ) exposure. Although a high methylation activity was found in C. farreri, it varied in different tissues with different inorganic As species exposure. The present results indicated that exposure to As (Ⅲ) and As (Ⅴ) could induce different responses in bioaccumulation and biotransformation in five tissues of C. farreri. Highlights: Biotransformation of waterborne inorganic arsenic in C. farreri was studied. Bioaccumulation capabilities of inorganic As in C. farreri related to As species. Detoxification strategy of As in C. farreri was studied by subcellular partition. High methylation activity in the gill and kidney were observed in C. farreri.